Smoke deposition and extraction in compartment fires with different ignition sources; Process Safety and Environmental Protection; Vol. 187 - Kuznetsov G. V. Geny Vladimirovich; Zhdanova A. O. Alena Olegovna; Volkov R. S. Roman Sergeevich; Strizhak P. A. Pavel Alexandrovich; Sviridenko A. S. Aleksandr Sergeevich (2024, 2024)
Title screen